Hubungan Tingkat Pengetahuan Akseptor terhadap Pemilihan Alat Kontrasepsi Hormonal di Desa Gedog Wetan - Ima Rusmawati; Rifzul Maulina (Lembaga Pengembangan Kinerja Dosen, 2025)
The proper selection of hormonal contraceptive methods is a crucial component in supporting the success of the Family Planning (FP) program. However, variations in knowledge levels among acceptors remain a major factor influencing the accuracy of contraceptive method choices. This study aims to analyze the relationship between the level of acceptors' knowledge and the selection of hormonal contraceptive methods in Gedog Wetan Village. A descriptive quantitative approach with a comparative design was used, involving two independent groups: an intervention group and a control group. A total of 30 women of reproductive age were selected using a total sampling technique. Data were collected through a structured questionnaire using the Guttman scale, and analyzed using the Independent Samples Test via SPSS version 22. The results showed a significant difference between knowledge levels and the accuracy of hormonal contraceptive selection (p = 0.000), with the intervention group that received educational sessions demonstrating more accurate choices compared to the control group. In conclusion, the level of knowledge significantly influences the selection of hormonal contraceptive methods. Therefore, structured and continuous education is essential to support rational decision-making in contraceptive use.